The Influence of Social Infrastructure on Visitor Satisfaction at the Betawi Cultural Village - Hilda Sari Wardhani; Rosandi Ardi Noegraha; Mutiara Nur Khiznatul Putri (Yayasan pendidikan dzurriyatul Quran, 2026)
Betawi Village is one of the cultural tourism destinations that offers a unique Betawi cultural experience to visitors. This study aims to analyze the impact of social infrastructure on visitor satisfaction at Betawi Village. Social infrastructure refers to public facilities such as toilets, places of worship, parking areas, seating, and information centers. The research method used is quantitative with a survey approach, where data is obtained through the distribution of questionnaires to 100 respondents, who are visitors to Betawi Village. Data analysis is conducted using multiple linear regression to determine the extent to which social infrastructure variables influence visitor satisfaction. The results of the study indicate that, collectively, social infrastructure has a significant effect on visitor satisfaction. Specifically, the toilet and seating facilities have the most dominant influence. These findings highlight the importance of managing and developing social infrastructure to enhance the quality of the tourist experience. This study is expected to provide input for destination managers in designing more effective service policies.